An analysis of the key stakeholders' perspective on the barriers in the implementation of China-Pakistan Economic Corridor (CPEC) energy projects - Altaf, Moaz; Weerakorn Ongsakul; Dhakal, Shobhakar; Ekbordin Winijkul; Bangchak Petroleum Public Company Limited Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
This qualitative research is based on the analysis of the key stakeholders{u2019} perspectives to identify the barriers in the implementation of China Pakistan Economic Corridor (CPEC) Energy projects. These key stakeholders who participated were Government Officials, people from Academia, businesspersons, people from public and private sectors, law firms and CPEC related think tanks and agencies. The goal was to identify all kinds of barriers and difficulties related to social, economic, environmental, technical and policy factors by analyzing the discourses (interviews) of the key stakeholders in the implementation of CPEC, which is part of Belt and Road Initiative (BRI). Most of the researchers in the past, seemed to have adopted the approach of focusing on the barriers related to one factor at a time. However, this research considered an overall holistic approach to identify these barriers and difficulties linked with all the above-mentioned factors in a single study to come up with the most prevalent barriers identified by doing the thorough analysis of the discourses (interviews) of the key stakeholders of CPEC in different professions from both Pakistan and China. Some of the barriers were pre-identified using the literature review while the rest of the barriers were uncovered after the interviews of the stakeholders. It was found that the most prevalent factors according to the stakeholders were the Poor Infrastructure Management, and Poor Policy Reforms and Poor Governance as most of the stakeholders voted for these 2 factors. A few stakeholders also voted for Internal Conflicts in Pakistan as one of the barriers in the implementation of CPEC Energy projects in Pakistan, while some of them helped to unearth new barriers, which were never discovered before like corruption, nepotism and incompetent people leading the Government institutions in Pakistan. The reasons for stakeholders{u2019} choices, were also included in this research.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy, School of Environment, Resources and Development
Research Studies Project Report (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Economic development -- Pakistan; Economic development -- China; Energy policy -- Pakistan; Energy policy -- China; Renewable energy sources -- Asia